Analysis of Factors Related to Spiritual Distress Among HIV/AIDS Patients - Anshar Rante; Djusmadi Rasyid; Warda Masta; Ismunandar Ismunandar (Poltekkes Kemenkes Palu, 2023)
The severity of the problems experienced by PLWHA (People Living with HIV/AIDS) can affect the psychological, social and spiritual aspects, as well as the ability and capacity of the health services. People living with HIV/AIDS experience psychosocial problems, such as anxiety towards illnesses they cannot predict. Patients commonly experience financial problems, chronic grief, depression, guilt, depression, and fear of death. Other psychosocial problems include withdrawal, impaired socialization, role disturbance, worry about relationships with partners, lifestyle changes, loss of enthusiasm due to limitations and feelings of alienation. This study aims to determine the factors related to spiritual distress among HIV/AIDS patients at Sawerigading General Hospital in Palopo. This was a quantitative study using a cross-sectional design. The study samples were selected using purposive sampling technique. Samples were selected among patients who came to the PCT unit of Sawerigading Hospital, Palopo City. The results showed that there was a relationship between self-relationship (p=0.005), relationship with others (p=0.024), art, music, literature and nature (p=0.024) and greater power (p=0.022) with spiritual distress. It can be concluded that there was a relationship between the independent variables of self-relationship, relationship with others, art, music, literature and nature, greater power with the dependent variable of spiritual distress.